Primary Prevention â Vaccination â New Era To Eradicate Cervical Cancer, Is It True Or Gimmick? - nuranna, laila (Indonesian Journal of Cancer, 2010)
Faculty member at Division of Gynecologic OncologyDepartment of Obstetrics and GynekologyFaculty of Medicine University of Indonesia îDr Cipto Mangunkusumo National General Hospital -JakartaGraduated from Faculty of Medicine University of Indonesia 1979.Finished from residency training in Obstetrics and Gynecologyat Faculty of Medicine UI/dr Cipto National General Hospital, 1986Received Doctoral degree at the same institutions, 2005Fellowship program from Gynecologic Oncology atGroningen university The Netherland/Academisch Ziekenhuiz Groningen, 1988Member of some Profesional Organization,Coordinator of Female Cancer Program Region JakartaFull text : http://www.scribd.com/doc/43595177/Primary-Prevention-Vaccination-New-Era-To-Eradicate-Cervical-Cancer-Is-It-True-Or-Gimmick